2015
DOI: 10.5935/0004-2749.20150095
|View full text |Cite
|
Sign up to set email alerts
|

Rebound tonometry versus Goldmann tonometry in school children: feasibility and agreement of intraocular pressure measurements

Abstract: Tonometry is fundamental to routine ophthalmological evaluation, and Goldmann applanation tonometry (GAT) is the gold standard method. Several devices, including the Perkins tonometer, Tono-Pen, Pascal tonometer (dynamic contour), and non-contact tonometer, can provide reliable values in adults (1)(2)(3)(4) . However, in general practice, intraocular pressure (IOP) measurement can be difficult in children due to a lack of cooperation. ABSTRACTPurpose: High intraocular pressure (IOP) is an important risk factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Even the studies that demonstrate good agreement between rebound tonometry, GAT and Tonopen note that greater variability exists at higher IOP and with variations in CCT [15][16]21] . Several studies have demonstrated a clear correlation between CCT and alterations in IOP readings with all forms of tonometry [24][25][26][27][28][29] . Tonnu et al [27] compared the effect of CCT on multiple methods of tonometry and noted that all methods of tonometry are significantly affected by CCT, however the effect is least with GAT.…”
Section: Resultsmentioning
confidence: 99%
“…Even the studies that demonstrate good agreement between rebound tonometry, GAT and Tonopen note that greater variability exists at higher IOP and with variations in CCT [15][16]21] . Several studies have demonstrated a clear correlation between CCT and alterations in IOP readings with all forms of tonometry [24][25][26][27][28][29] . Tonnu et al [27] compared the effect of CCT on multiple methods of tonometry and noted that all methods of tonometry are significantly affected by CCT, however the effect is least with GAT.…”
Section: Resultsmentioning
confidence: 99%
“…When interpreting the IOP values with slightly increased pachymetry values, it must be considered that the values can be overestimated, especially in the case of IOP measurements with rebound tonometry. In a study with mean pachymetry of 558 ± 36 μm, values were approximately 2 mmHg higher with rebound tonometry than with Goldmann applanation tonometry in children [ 27 ]. It can therefore be assumed that the partly substantially increased IOP values are not solely attributable to rebound tonometry.…”
Section: Discussionmentioning
confidence: 99%
“…It can therefore be assumed that the partly substantially increased IOP values are not solely attributable to rebound tonometry. Furthermore, it must be taken into account that, especially in children, the measurement with Goldmann applanation tonometry is often not feasible; failure rates of up to 26% have been described [ 27 ].…”
Section: Discussionmentioning
confidence: 99%